Aetiological factors of molar incisor hypomineralization - Janković Svjetlana; Ivanović Mirjana; Davidović Bojana; Lečić Jelena (Serbian Medical Society - Dental Section, Belgrade, 2013)
Introduction. Teeth hypomineralization that involves molars only, or molars and incisors is known as disease Molar Incisor Hypomineralization (MIH). Aetiology of MIH is not known, however, factors responsible for this disease are present in the first year of life. The aim of this research was to identify possible aetiological factors responsible for the occurrence of this disease. Material and Methods. The study included eight years old children from the municipality of Foca. Parents who gave their consent for the participation of children in the study completed a questionnaire in which they listed aetiological factors described in the literature to be responsible for the emergence of hypomineralization. Modified DDE index (Modified DDE Index for Use in Epidemiological Surveys) was used to estimate hypomineralization on all teeth; however, MIH changes were classified separately. Results. More than ninety different factors may be responsible for enamel defects. Possible aetiological factors listed in the literature are: premature birth, low weight of newborns, hypoxia, metabolic disorder of calcium and phosphate, fever, genetic factors, etc. Results did not confirm statistical significance for any of examined aetiological factors. Conclusion. In this study a retrospective analysis of data was performed. Etiological factors of MIH were identified but the most responsible for MIH were not determined.